2010
DOI: 10.1074/jbc.m110.103127
|View full text |Cite
|
Sign up to set email alerts
|

Erk5 Activation Elicits a Vasoprotective Endothelial Phenotype via Induction of Krüppel-like Factor 4 (KLF4)

Abstract: The MEK5/Erk5 MAPK cascade has recently been implicated in the regulation of endothelial integrity and represents a candidate pathway mediating the beneficial effects of laminar flow, a major factor preventing vascular dysfunction and disease. Here we expressed a constitutively active mutant of MEK5 (MEK5D) to study the transcriptional and functional responses to Erk5 activation in human primary endothelial cells. We provide evidence that constitutive Erk5 activation elicits an overall protective phenotype cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
135
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(143 citation statements)
references
References 50 publications
(56 reference statements)
6
135
2
Order By: Relevance
“…These results are consistent with those from previous studies showing simvastatin induced KLF4 expression and a shift to vasoprotective phenotype via the activation of the MEK5/ Erk5 cascade in human primary ECs. 31 Moreover, Maejima et al 32 also showed that pitavastatin induced KLF4 expression, accompanied by the chromatin structure changes in the promoterenhancer region of the KLF4 gene in HUVECs. Further studies on the mechanism by which statins induce KLF4 expression may shed light on novel therapeutic targets for treating and preventing ischemic AKI and other vascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with those from previous studies showing simvastatin induced KLF4 expression and a shift to vasoprotective phenotype via the activation of the MEK5/ Erk5 cascade in human primary ECs. 31 Moreover, Maejima et al 32 also showed that pitavastatin induced KLF4 expression, accompanied by the chromatin structure changes in the promoterenhancer region of the KLF4 gene in HUVECs. Further studies on the mechanism by which statins induce KLF4 expression may shed light on novel therapeutic targets for treating and preventing ischemic AKI and other vascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Since ERK5 has been a focus of interests in cardiovascular diseases, we searched the literature in the vascular system and found that KLF4 has been reported to be an important mediator for ERK5 (Ohnesorge et al 2010;Clark et al 2011;Sunadome et al 2011). Importantly, NGF has been reported to transiently up-regulate KLF4 mRNA level in PC12 cells (Dijkmans et al 2009).…”
Section: Ngf and Pc Up-regulated The Expression Of Klf4mentioning
confidence: 99%
“…While there is considerable information regarding ERK5's upstream activators, little is known regarding the downstream effectors of ERK5, especially in the CNS. In a recent report by Ohnesorge et al, transcription factor Krüppel-like factor 4 (KLF4) was identified as a novel executioner of MEK5/ERK5 pathway to elicit an antiapoptotic and anti-inflammatory phenotype in human endothelial cells (Ohnesorge et al 2010). KLF4 is well known for its role in stem cell biology (Takahashi and Yamanaka 2006), cardiovascular disease (Dong and Huang 2009) and cancer (Cho et al 2007;Akaogi et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptional activation of KLF2 triggers induction of anti-inflammatory genes including eNOS and reduction of proinflammatory genes including cytokines (13,14). In addition to KLF2, ERK5 activation induces the expression of KLF4-dependent genes, which are also important in flow-mediated EC-protective responses (15,16). Taken together, a growing body of evidence suggests ERK5 as an emerging upstream signaling molecule in flow-mediated atheroprotective responses.…”
Section: * This Work Was Supported By the Basic Science Research Progmentioning
confidence: 91%